Pathogenic role of monocytes/macrophages in large vessel vasculitis - Watanabe, Ryu; Hashimoto, Motomu (Frontiers in Immunology, 2022)
Vasculitis is an autoimmune vascular inflammation with an unknown etiology and causes vessel wall destruction. Depending on the size of the blood vessels, it is classified as large, medium, and small vessel vasculitis. A wide variety of immune cells are involved in the pathogenesis of vasculitis. Among these immune cells, monocytes and macrophages are functionally characterized by their capacity for phagocytosis, antigen presentation, and cytokine/chemokine production. After a long debate, recent technological advances have revealed the cellular origin of tissue macrophages in the vessel wall. Tissue macrophages are mainly derived from embryonic progenitor cells under homeostatic conditions, whereas bone marrow-derived circulating monocytes are recruited under inflammatory conditions, and then differentiate into macrophages in the arterial wall. Such macrophages infiltrate into an otherwise immunoprotected vascular site, digest tissue matrix with abundant proteolytic enzymes, and further recruit inflammatory cells through cytokine/chemokine production. In this way, macrophages amplify the inflammatory cascade and eventually cause tissue destruction. Recent studies have also demonstrated that monocytes/macrophages can be divided into several subpopulations based on the cell surface markers and gene expression. In this review, the subpopulations of circulating monocytes and the ontogeny of tissue macrophages in the artery are discussed. We also update the immunopathology of large vessel vasculitis, with a special focus on giant cell arteritis, and outline how monocytes/macrophages participate in the disease process of vascular inflammation. Finally, we discuss limitations of the current research and provide future research perspectives, particularly in humans. Through these processes, we explore the possibility of therapeutic strategies targeting monocytes/macrophages in vasculitis.